ZOOPLANKTON DYNAMICS OF LAKE KUMSULTAN - Sanoyeva Khosiyat Ortiq qizi (Web of Journals Publishing, 2025)
Through this article, we have revealed the species composition of zooplankton in Lake Kumsultan and the methods for determining it. Based on this, we can see what the biomass of zooplankton is.
Keywords: Species composition of zooplankton, biomass of zooplankton, coefficient of zooplankton.